Effects of exercise on body mass index and waist circumference of individuals with intellectual and developmental disabilities: a systematic review with meta-analysis - Jacinto, Miguel; Monteiro, Diogo; Antunes, Raul; Ferreira, José Pedro; Matos, Rui; Campos, Maria João (Frontiers in Physiology, 2023)
This systematic review with meta-analysis aims to assess the magnitude of the effects of physical exercise programs on body mass index (BMI) and waist circumference (WC) of individuals with Intellectual and Developmental Disabilities (IDD), metabolic and cardiovascular health markers. Considering the eligibility criteria, a final sample of nine articles was obtained. For BMI, the Z-value obtained to test the null hypothesis (difference between means is zero), showed a Z=-2.176 and p=0.03. The highest magnitude of the effect was from the intervention with combined training (difference in means: -0.399), with a value of Z=-1.815 and p=0.07. For WC, the Z-value is zero, showing a Z=-3.306 and p=0.001. The highest magnitude of the effect was from the intervention with continuous cardiorespiratory training of -0.786, with a value of Z=-2.793 and p=0.005. Physical exercise prevents increases in BMI and WC in individuals with IDD. Aerobic training seems to be more effective in promoting WC and combined training in BMI. This is a provisional file, not the final typeset article compared to the general population (3). Excessive adiposity results from an imbalance between energy intake and expenditure.